GAMBARAN KASUS PERSALINAN SEKSIO SESAREA DI RSUD Dr.SOEDARSO PONTIANAK TAHUN 2010 - ., Novita Sari (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Maternal Mortality Rate (MMR) in Indonesia is still far uponMillenium Develompment Goals target. Cesarean delivery has played amajor role in lowering MMR but also has risk of various complications.Objective: To know the cesarean section rate (CSR) in dr.Soedarsogeneral hospital Pontianak, to know the characteristics of mothers basedon age, parity, frequency of ANC, and referral status, to know theindications and outcomes of CS based on length of hospital treatment,complications, and Apgar scores.Method: This research was a descriptive study which was conducted byusing secondary data from medical records.Result:CS was performed in 674 patiens from 1505 total delivery indr.Soedarso general hospital Pontianak in 2010. Most patients were in theage 25-29 years (25.4%), primigravida (44.4%), had antenatal care visitfour times or more (73.7%), and were referred from other facilities(66.1%). The most common indication of CS was cephalopelvicdisproportion (27.9%). Most of patiens (51,8%) stayed for 4-5 days inhospital, three percent of cases had complication, which the most commoncomplication was surgical wound infection (1.8%). There were 9,3% ofasphyxia babies.Conclusions: CSR in dr.Soedarso general hospital Pontianak was44,78%. CSwas oftenperformed inpatients who aged25-29 years old,primigravida, have ANC visits 4 times or more, and referred by otherhealth facilities. Length of hospital stay was affected by complications.Asphyxiain newborn was affected bypoorpatientinput.